MODERN LITERARY INTERPRETATIONS OF THE CATEGORY OF IRONY - Kadirova N (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article examines the experience accumulated in fiction of expressing irony in the domestic literary criticism of the XX-XXI centuries. Irony is considered in the light of the theory of the comic, various types and ways of expressing irony associated with the use of details are traced.